'The Train Has Left the Station': The Project on Emerging Nanotechnologies and the Shaping of Nanotechnology Policy in the United States. - Michelson, Evan S. (Review of Policy Research, 2013)
The purpose of this paper is to analyze the efforts of the Project on Emerging Nanotechnologies ( PEN) in seeking to influence nanotechnology policy in the United States. Using the conceptual framework of anticipatory governance to guide the analysis, a series of strategies that PEN adopted will be described, including leveraging external expertise, developing cross-disciplinary research products, providing a future-oriented view on policy analysis, and building a brand for communications and outreach. This case study is a useful example in demonstrating the recent conceptual shift away from relying on government-led technology assessment efforts to consider the longer-term implications of new technologies toward the concept of anticipatory governance that includes a more substantive role for nongovernmental actors, that in providing forward-looking, actionable intelligence for decision makers. Considering the example of PEN also highlights the critical role that boundary-spanning organizations play in linking together disparate communities of expertise.